PENGARUH PENERAPAN MODEL PEMBELAJARAN EXAMPLES NON EXAMPLES DISERTAI POWER POINT TERHADAP HASIL BELAJAR BIOLOGI KELAS XI SMAN 1 LEMBAH MELINTANG PASAMAN BARAT - Handayani, Destri - (Pendidikan Biologi, 2014)
This research is conducted because the result of students in XI class at SMAN 1Lembah Melintang West Pasaman especially in studying biology is low. It is caused by several factors such as, first the stategy that is implemented by the teacher is not interesting, second, the student lack of motivation and interesting to study. The purpose of this research is to find out the effect of examples non examples by using power pointto word students achievement in studying biology in XI class at SMAN 1 LembahMelintang West Pasaman. The design of this research is experimental research by using âRandomized Control Group Posttest only Designâ. After conducting this research, the researcher find that the achievement of students in experiment class is higher than control class. The average of students achievement in experiment class is about 76,74 meanwhile control class is 65,56. The result of this reseach find that thitung 2,79 >ttabel 1,67 it means that H1is accepted (the effect of examples non examples by using power point at students achievement in learning biology at XI class in SMAN 1 Lembah Melintang West Pasaman). It can be said that examples non examples by using power point can increase students achievement in learning biology at XI class at SMAN 1 LembahMelintang West Pasaman.